Oral Peer Feedback in Online Speaking Class: Implementation, Students’ Attitudes, Preferences, and Usefulness - Shelia Anjarani; Yupitasari Alvianingrum (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
This study examines the views of students studying English in one of the English Language Education Study Programmes on the oral peer feedback they gave and received in an online English-speaking class. The online speaking class was observed to know the implementation of oral peer feedback. Thirty-eight students who were enrolled in the course completed a questionnaire, and afterward, four of these students participated in a semi-structured interview. The results obtained from the questionnaire indicated that students derived satisfaction from both giving and receiving oral feedback. Students also preferred to give and receive positive feedback. The students found that providing and receiving oral feedback benefited their learning process. In contrast, it was found that students indicated a stronger preference for providing affective feedback than cognitive and constructive feedback. The interview responses shed light on the reasons underlying these perceptions. The study also offers pedagogical insights related to implementing oral peer feedback in online speaking classes.